The Complete Codes and Statutes of the State of Montana 1084, § 758 (1895) - (:unkn) unknown (My University, 1895)
Pt. 1, tit. 11, § 758: Every person who within the limits of any city or town carries or bears concealed about his person a dirk, dagger, pistol, revolver, or other deadly weapon is punishable by a fine not exceeding one hundred dollars. This Section does not apply to peace officers in discharge of their official duty.
Keywords: CARRY - CONCEALED